2019
DOI: 10.3389/fgene.2019.00454
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omic Analysis of the Microbiome and Metabolome in Healthy Subjects Reveals Microbiome-Dependent Relationships Between Diet and Metabolites

Abstract: The human microbiome has been associated with health status, and risk of disease development. While the etiology of microbiome-mediated disease remains to be fully elucidated, one mechanism may be through microbial metabolism. Metabolites produced by commensal organisms, including in response to host diet, may affect host metabolic processes, with potentially protective or pathogenic consequences. We conducted multi-omic phenotyping of healthy subjects ( N = 136), in order to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 72 publications
3
121
0
Order By: Relevance
“…Tang and colleagues [51] applied metabolomics and metagenomics analyses to study usual dietary intake in healthy participants (Table 1). In addition to identifying associations between diet and metabolites, they conducted analyses to define inter-relationships between diet, the microbiome and metabolome and additional analyses to determine whether identified associations were mediated by microbial enterotype.…”
Section: Biomarkers Diet and Cancermentioning
confidence: 99%
“…Tang and colleagues [51] applied metabolomics and metagenomics analyses to study usual dietary intake in healthy participants (Table 1). In addition to identifying associations between diet and metabolites, they conducted analyses to define inter-relationships between diet, the microbiome and metabolome and additional analyses to determine whether identified associations were mediated by microbial enterotype.…”
Section: Biomarkers Diet and Cancermentioning
confidence: 99%
“…Many scientists are now interested in studying the correlative relationships between microbes and metabolites (e.g., [1,2,3,4]). However, these kinds of analyses are complicated by the compositional (i.e., relative) nature of the data [5,6].…”
Section: Responsementioning
confidence: 99%
“…Previous studies showed that the phenotypic traits of ruminants were affected by rumen microbiota, whose functions could be re ected by the ruminal metabolites [23][24][25]. However, most studies have only focused on the single change of dietary protein/energy and few reports studied the comprehensive effects of dietary energy and protein on the rumen bacterial composition and rumen metabolites [3,16,18,22,26,27].…”
Section: Introductionmentioning
confidence: 99%